Factors associated with diarrheal disease among children aged 1-5 years in a cholera epidemic in rural Haiti. - Hilary A Dolstad (Public Library of Science (PLoS), 2021)
Diarrheal illness is a major cause of morbidity and mortality among children in Haiti, and the impact of diarrheal illness was compounded by a cholera outbreak between 2010 and 2019. Our understanding of risk factors for diarrhea among children during this outbreak is limited. We conducted a secondary analysis of data collected as part of a cholera vaccine effectiveness study to identify factors associated with medically attended diarrhea among children in central Haiti from October of 2012 through November of 2016. We identified 47 children aged one to five years old who presented to medical clinics with acute, watery diarrhea, and 166 matched controls who did not have diarrhea, and we performed conditional logistic regression to identify factors associated with diarrhea. Discontinuing exclusive breastfeeding within one month of birth was associated with increased risk of diarrhea (RR 6.9, 95% CI 1.46-32.64), and diarrhea was inversely associated with reported history of supplementation with vitamin A (RR 0.05, 95% CI 0.004-0.56) and zinc (reported among 0% of cases vs. 17% of controls). Because of the concordance in supplementation patterns, it was not possible to attribute the association to vitamin A or zinc independently. While having a respondent who correctly identified ≥3 means of avoiding cholera was associated with reduced risk of diarrhea (RR 0.43, 95% CI 0.19-1.01), reported household sanitation practices and knowledge of cholera were not consistently associated with risk of diarrhea. These findings support ongoing efforts to reduce barriers to breastfeeding and promote pediatric supplementation with vitamin A and zinc in Haiti. Given the reduced efficacy of current oral cholera vaccines (OCV) among children, the results reinforce the importance of breastfeeding and micronutrient supplementation in preventing all-cause pediatric diarrheal illness generally and during cholera outbreaks.